THE TENDENCY OF ACCOUNTING FRAUD IN MEDIATION INFLUENCE OF INTERNAL CONTROL AND INFORMATION ASYMMETRY ON ORGANIZATIONAL ACCOUNTABILITY - Aini Indrijawati; Nichen Nichen; Kartini Kartini (Mega Aktiva, 2019)
This study aimed to get empirical evidence about the mediation tendency of the accounting fraud at the influence the effectiveness of internal control and the information asymmetry on accountability organization. Empirical studies conducted on six Polytechnic State in Makassar namely Politeknik Negeri Ujung Pandang, Makassar ATI Polytechnic, the Polytechnic Studies Polytechnic Sailing and Tourism. Methods of data collection using the questionnaire technique. The number of samples in this study were 59 respondents were selected based on purposive sampling method. This study uses analysis techniques Linear Regression with SPSS version 23.0. The results showed a positive relationship between the asymmetry of information with the tendency of accounting fraud in this sense that, each accounting fraud will likely increase if the asymmetry of information often occurred in an agency. The implication of this research is the asymmetry of information, it will trigger the action of fraud by staff. In this case led back to spearhead the tendency determining whether fraud could be minimized or not. Any information relating to the agencies should be communicated to the staff equally, according to their respective fields. Provision of information equally to the staff of each, will foster a sense of responsibility on the staff. If the sense of responsibility towards work has grown.